Context-dependent categorisation of vowels: a mismatch negativity study of positional neutralisation. Issue 2 (4th February 2020) - Rodrigues Silva, Daniel Márcio; Rothe-Neves, Rui
ABSTRACT: Studies exploring the mismatch negativity (MMN) response to speech sounds have identified neural activity associated with processing of phonologically distinctive information and language-specific perceptual categorisation. Yet little attention has been given to a basic fact of phonology, namely, that not all phoneme distinctions in a language are functional in all phonological contexts. The present ERP study explores a case in which the low-mid versus high-mid vowel distinction is limited to stressed syllables, resulting in category merger elsewhere – i.e. "positional neutralisation". We provide evidence that the sensitivity of MMN generator processes to vowel distinctions parallels their position-dependent phonological status (functional versus neutralised). As an additional finding, the MMN peaked earlier for stressed than for unstressed distinctions, indicating that stress facilitates automatic auditory discrimination. The results fit neatly into models assuming that MMN reflects a mismatch between a deviant stimulus and an abstract representation of standards that omit phonologically non-distinctive information.